Interpretation of Cyclic Form in Bach’s “Goldberg Variations” through Performance History - Majid Motavasseli (Zeitschrift der Gesellschaft für Musiktheorie)
Based on quantitative and qualitative analyses of seventy-six selected recordings spanning the years 1928 to 2020, this article examines the extent to which performers interpret the “Goldberg Variations” as a cycle. To that end, possible tempo relations between the pieces have been analyzed through measurements of initial tempi, focusing on three categories: (1) progression (subsequent variations 24, 25, and 26), (2) structure (variations in a minor key: 15, 21, and 25), and (3) architectonic position (beginning and end of the cycle: Aria 1, variations 1 and 30, and Aria 2). The analytical results confirm a distinct tendency to implement tempo relations in the cycle and suggest that, with the exception of both performances of the Aria, such relations are implemented more frequently in the case of linear connections (between subsequent pieces) than between pieces with a strong structural relationship.